Accurate Ab Initio Potential Energy Curve of $X^2Π$ State and High-Temperature $A^2Δ$-$ X^2Π$ Fluorescence Spectra for CH Radical (Journal of Atomic and Molecular Sciences, 2021)
In present study an accurate ab initio potential energy curve of $CH(X^2Π)$ has been determined at the complete basis set limit. The core-valence corrections and relativistic corrections including scalar relativity and spin-orbit coupling are determined. The vibrational and rotational levels are calculated based on fitted potential energy curve. Total 19 vibrational levels are found for $^{13}CH$ ground state, and comparing with available experimental data, the deviation is less than 15 $cm^{-1}.$ The dissociation energy is calculated within 50 $cm^{-1}$ of the experimental value 29358 $cm^{-1}.$ The $A^2Δ$ - $X^2Π$ electric transition dipole moment function is calculated, and the high-temperature fluorescence spectra arising from $A^2Δ$ - $X^2Π$ transition are simulated.